The Validation and Further Development of the Multidimensional Cognitive Load Scale for Physical and Online Lectures (MCLS-POL) - Andersen, Martin S.; Makransky, Guido (Frontiers in Psychology, 2021)
Cognitive load theory (CLT) has been widely used to help understand the process of learning and to design teaching interventions. The Cognitive Load Scale (CLS) developed by Leppink et al., (2013) has emerged as one of the most validated and widely used self-report measures of intrinsic load (IL), extraneous load (EL), and germane load (GL). In this paper we investigated an expansion of the CLS by using a multidimensional conceptualization of the EL construct that is relevant for physical and online teaching environments. The Multidimensional Cognitive Load Scale for Physical and Online Lectures (MCLS-POL) goes beyond the CLS’s operationalization of EL by expanding the EL component which originally included factors related to instructions/explanations with sub-dimensions including EL stemming from noises, and EL stemming from both media and devices within the environment. Through three studies, we investigated the reliability, and internal and external validity of the MCLS-POL using the Partial Credit Model, Confirmatory Factor Analysis, and differences between students either attending a lecture physically or online (Study 2 and 3). The results of Study 1 (N = 250) provide initial evidence for the validity and reliability of the MCLS-POL within a higher education sample, but also highlighted several potential improvements which could be made to the measure. These changes were made before re-evaluating the validity and reliability of the measure in a new sample of higher education psychology students (N = 140, Study 2), and psychological testing students (N = 119, Study 3). Together the studies provide evidence for a multidimensional conceptualization cognitive load and provide evidence of the validity, reliability, and sensitivity of the MCLS-POL and provide suggestions for future research directions.